Theoretical Foundations of Accounting for Finished Medicinal Products: International and National Aspects (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
In this article, on the basis of the characteristics of the production of ready-made medicinal products, their theoretical basis, similar and different aspects based on international and national standards, the shortcomings in their production and their elimination are discussed to increase the economic efficiency of enterprises engaged in this field. Recommendations are presented.